Assessment of right atrial function in inferior wall AMI - Abhijit Das; Lipika Adhikari; Sandip Sarkar (Asian Journal of Medical Sciences, 2022)
Background: Approximately 30–50% of patients with inferior infarction have some involvement of the right ventricle. The right ventricular (RV) infarction almost invariably develops in association with a large infarction of the adjacent septum and inferior 0 walls, but isolated infarction of the right ventricle is seen in just 3–5% of autopsy-proven cases of MI. This study is designed to assess the right atrial (RA) functions in inferior wall acute myocardial infarction (AMI) (IWMI) echocardiographically and to compare it with patients who do not have history of ischemic heart disease (IHD) but having risk factors for IHD.